A auditoria externa e as demonstrações contábeis no direito comercial - Pereira, Alexandre Demetrius (Universidade de São Paulo, 2010)
A auditoria externa de demonstrações contábeis é um dos instrumentos mais importantes para o desenvolvimento do mercado, pelo fato de adicionar credibilidade e segurança às informações financeiras prestadas pelos agentes econômicos que buscam captar recursos junto ao público investidor. A doutrina jurídica pátria, entretanto, ao contrário do que ocorre em outros países, tem relegado o estudo do assunto a um papel secundário, quase não abordado nas obras nacionais, deixando sua pormenorização integralmente sob o domínio da ciência contábil. Esta postura causa um afastamento do jurista da realidade das circunstâncias em que a auditoria se desenvolve, fazendo com que, pela falta de compreensão das peculiaridades da matéria, haja a aplicação inadequada de muitos institutos a uma realidade específica e, muitas vezes, diversa daquela para as quais referidos institutos foram concebidos. Como a matéria abrange tanto o Direito quanto a Contabilidade, tencionamos fazer aqui uma abordagem conjunta, a fim de possibilitar a comunicação das duas ciências e compartilhar os problemas que o tema apresenta. Passamos em revista a natureza dos principais institutos de auditoria; seu relacionamento e importância na economia; as características jurídicas do contrato, suas obrigações, as partes contratantes e os terceiros interessados; o desenvolvimento contábil de sua execução; e seu relacionamento com os sistemas de governança corporativa. Além disso, verificamos as atuais tendências quanto ao sistema de riscos e responsabilidade civil do auditor, matéria amplamente discutida no âmbito internacional.
Keywords: Accounting and legal repercussions; Audit contract; Audit externe; Auditoria; Auditoria externa; Auditors liability; Balance comptable; Balanço contábil; Comptabilité; Contratos; Demonstração financeira; Direito comercial; Droit commercial; Etat financier; External audit; Governança corporativa; Responsabilidade civil; Responsabilité de l'auditeur

Teoria palco-platéia: a interação entre regulação e autorregulação do mercado de bolsa - Calabró, Luiz Felipe Amaral (Universidade de São Paulo, 2010)
A tese a ser defendida é a de que a autorregulação institucionalmente estruturada e legitimada pela regulação é um eficiente arranjo para tratar as falhas e riscos inerentes ao mercado de bolsa. O trabalho se inicia com a descrição da atual estrutura da autorregulação do mercado de bolsa, destacando seu novo formato institucional decorrente do processo de desmutualização e abertura de capital das entidades administradoras do mercado de bolsa e concluindo pela necessidade de adoção de novas perspectivas sobre o tema que transcendam o aparente antagonismo entre concepções liberais e intervencionistas. A partir dessa premissa, o trabalho apresenta uma visão panorâmica da evolução histórica da autorregulação do mercado de bolsa e considerações sobre os conceitos de autorregulação em outras áreas do conhecimento, a fim de identificar suas variações e seus elementos mais marcantes que constituirão a base a partir da qual serão apresentadas as novas perspectivas de análise do tema. As perspectivas propostas enfocam a natureza jurídica da autorregulação do mercado de bolsa como atividade paraestatal destinada a concretizar o modelo teórico neoclássico de justa formação dos preços segundo a livre atuação das forças de oferta e demanda e, também, melhorar os padrões de conduta praticados no mercado. Para tanto, o trabalho propõe que as decisões tomadas no âmbito da autorregulação se pautem por critérios materiais baseados nas premissas teóricas da concorrência perfeita e na exigência de cumprimento dos deveres derivados da boa-fé objetiva (informação, lealdade e proteção). Por fim, é apresentada uma especulação teórica, preliminar e não definitiva, denominada teoria palco-platéia, que visa situar o desenvolvimento da estrutura de autorregulação do mercado de bolsa como parte de uma questão essencial de interação entre indivíduo e sociedade representada nas diversas situações comunicativas envolvidas nos processos decisórios individuais e coletivos que modelam os padrões de conduta e as instituições públicas e privadas.
Keywords: Autorégulation; Bolsa de valores; Direito comercial; Equities; Exchange market; Marché boursier; Mercado de capitais; Mercado futuro; Regulation; Régulation; SRO; Securities; Self-regulation; Self-regulatory organizations; Stage-audience; Stock Exchange

The suitability of the South African corporate tax regime for the use of South African resident intermediary holding companies - Legwaila, Thabo (University of Pretoria, 2010)
An Intermediary Holding Company (“IHC”) is a company that is interposed between an ultimate holding company and the operating subsidiaries of a group of companies. The IHC operates at an international level such that either its holding company or its subsidiaries or both are located in a country foreign to the IHC. Its main functions are to acquire, manage and dispose of the assets of the group of companies and to facilitate structural flexibility of a group of companies. Investors have tax and non-tax reasons for conducting business using an IHC, and, depending on the reasons, they determine the location of the IHC based on the characteristics of potential host countries. This thesis analyses the suitability of the South African corporate tax regime for the use of South African-resident Intermediary Holding Companies. The South African government has the objective of promoting South Africa as a gateway for investment in Africa and for this reason the present research is important. Such an objective could be adversely affected by a corporate tax regime that is not suitable for the operations of an IHC. Furthermore, the Katz Commission recommended in 1997 that South Africa should consider introducing a regime that is suitable for the location of holding companies. In discharging its functions the IHC attracts liability for corporate income tax, capital gains tax, controlled foreign company tax and dividends tax. It also exposes itself to anti-avoidance measures such as thin capitalisation and transfer pricing provisions. The existence of such taxes and anti-avoidance measures in the tax system of a country may deter investors from locating an IHC in such country. Exchange control regulations could also adversely affect the ability of the IHC to perform its functions effectively, as their purpose is to restrict the movement of capital out of the country. The South African legal system contains all these taxes and anti-avoidance measures as well as exchange control provisions. However, it also contains tax instruments that alleviate the tax burden on an investor using an IHC such as the participation exemption, advance tax rulings and a network of tax treaties. Against this background this thesis analyses the South African corporate tax system to determine whether it is suitable for locating an IHC. In the analysis, a comparative study is done of the tax systems of two of the most effective IHC host countries, namely the Netherlands and Mauritius. In addition, a brief discussion of the special features contained in the tax systems of Belgium, Ireland and the United Kingdom outlines why these jurisdictions are not necessarily successful in attracting IHCs. The thesis also discusses harmful tax practices and the attitude of the international community towards countries that engage in harmful tax competition in order to determine the limits to which a country should use the tax system to attract investment. Finally, the thesis makes recommendations as to what adjustments could be made in order to enhance the suitability of South Africa to host an IHC. The thesis recommends a special dispensation as regards corporate income tax and exchange control that would apply to wholly-owned South African companies that own foreign subsidiary shares and loans that consist of 80% of the gross asset total of these companies.
Keywords: Intermediary Holding Company; South Africa; Tax; Taxation

La régulation des marchés financiers dans l'espace OHADA - Keuffi, Daniel Ebénézer (Université de Strasbourg ; Université Dschang, 2010)
L'apparition des marchés financiers dans le paysage économique et financier des États membres de l'espace OHADA vers la fin des années 1990 a débouché sur la nécessité de mettre sur pied des règles et des structures d'encadrement à la fois nouvelles et fonctionnelles. Soucieux de faire des marchés financiers des facteurs clés de leurs politiques de développement, les pouvoirs publics se sont très tôt imposés comme des maillons incontournables des processus de création et de fonctionnement de ces marchés. Cette omniprésence des pouvoirs publics a contribué à l'émergence d'un schéma novateur et sans précédant, à savoir la mise sur pied de marchés financiers et d'organes d'encadrement à vocation communautaire. Toutefois, pour atteindre l'efficacité recherchée, les nouvelles structures d'encadrement doivent trouver à s'articuler avec les dispositifs juridiques et institutionnels existant tant aux niveaux régionaux qu'aux niveaux nationaux. De même, un juste équilibre doit être trouvé entre les intérêts légitimes des investisseurs étrangers et les ambitions de développement économique des États concernés. The appearance of financial markets in the economic and financial landscape of the Member states of the OHADA space towards the end of 1990s resulted in the necessity of setting up rules and supervisory structures at once new and functional. Worried of making financial markets a leading instrument of their development policies, public authorities very early positioned themselves as essential actors of the processes of creation and functioning of these markets. This omnipresence of public authorities contributed to the emergence of an innovative and unprecedented scheme: The setting up of financial markets and supervisory structures with community vocation. However, to achieve the desired efficiency, the new supervisory structures must be adapted to the legal and institutional arrangements existing both at regional and national levels. Also, a just balance must be found between the legitimate interests of foreign investors and the ambitions of economic development of the concerned States.

Impact of Macro and Micro Governance Structures on Earnings Management - Houqe, Muhammad Nurul (Victoria University of Wellington, 2010)
This study examines the macro and micro level determinants of the quality of reported earnings. The prior literature suggests that both micro and macro variables impact on discretionary accruals choice in managing earnings. However, most of the studies on earnings management have been single country studies that have focussed only on micro variables as all firms within the samples examined have been subject to the same interplay of macro economic, legal, cultural and institutional frameworks. This study addresses this gap in the literature by using a sample of 156,906 firm year observations from 63 countries over the period 1998-2007 to examine the role of thirteen micro and macro variables in determining earnings quality. The macro variables studied include legal enforcement, political system, and control of corruption, culture and adoption of IFRS. Earnings management is estimated using the modified Jones model (Dechow et al. 1995) in a cross section (DeFond and Jiambalvo 1994; Francis et al. 1998). The results of the study indicate that macro and micro level variables have a strong impact on earnings management behaviour and thus earnings quality. The limits imposed by a country's legal, cultural and institutional setting on managerial discretionary accruals choices, strongly impact the quality of reported earnings. Future research on earnings management should therefore control both micro and macro level variables.
Keywords: Earnings management; Macro governance; Micro governance